Low Temperature Induction of Hormonal Sensitivity in Genotypically Gibberellic Acid-Insensitive Aleurone Tissue - Singh, Surinder Pal (1984)
An exposure of genetically gibberellic acid-insensitive isolated wheat aleurone tissue/deembryonated seeds to low temperature for 20 hours prior to addition of exogenous gibberellic acid results in a significant increase in sensitivity to gibberellic acid. The results may reflect a low temperature-induced increase in hormone receptor sites and could have important implications for elucidating the nature of the primary site of hormone action.